Demo Buruh Menolak Kenaikan Harga BBM dalam Fotografi Jurnalistik - Hasiholan, Yohanes; Novianti, Erlina; Aurelia Tahalea, Silviana Amanda (Pascasarjana Institut Seni Indonesia Padang Panjang, 2024)
There was a demonstration of workers refusing to increase fuel prices in the Arjuna Wijaya Horse Statue Area, Central Jakarta, on October 10, 2022. This situation also closed the Medan Merdeka Barat Road. The author is interested in documenting labour demonstrations using journalistic photography. It is one of the communication media that combines verbal and visual elements. Verbal elements in the form of words called caption, and visual elements aims to complete the information of an image. The reason is that a photo without a caption can lose the meaning. Technical of taking picture used the EDFAT method to add variety to the composition of each photo and help to determine the important things that need to be captured. This study aims to document the situation of labour demonstrations using the EDFAT method in journalistic photography, which provides factual information about an incident. The research method used by the author is observation and literature study. Observations was carried out by observing journalistic photographs created by Henri Cartier-Bresson and M Risyal Hidayat. Literature study was conducted by reading journals and books about photojournalism. The results of the study involved the work of photo documentation about labour demonstration using the EDFAT method and the decisive moment theory in capturing the decisive moment with accuracy, reading the situation, and setting the composition. This study concludes that the use of the EDFAT method is quite useful for photojournalism shooting because it helps photographers to capture important things, for example, the entire that includes the whole place.